Are robots coming to take the jobs of dental support staff? Ai applications in business management of dental practices - Alessandro Quaranta; Wang Lai Hui (Annali di Stomatologia)
The integration of artificial intelligence (AI) in dental practices is transforming traditional business management roles. This article examines the impact of AI on support staff positions such as practice managers, dental assistants, administrative personnel, and receptionists. By exploring current AI applications— including scheduling, billing, patient communication, inventory management, and marketing—the study assesses the benefits and challenges of AI adoption. It includes fundamental definitions of AI concepts to provide clarity. The article concludes that while AI enhances operational efficiency and patient service quality, the complete replacement of human staff is unlikely due to the interpersonal and complex nature of dental care. The discussion emphasizes the need for a strategic approach to AI integration, highlighting the evolving collaboration between humans and machines in the dental sector.